Identification of Rossby Atmosphere-Tropical Cyclone in Eastern Indonesian Waters - Suhendar, Maldiva Hafiza Anjarika; Yulihastin, Erma; Syalsabilla, Alya Fitri; Azzahra, Syifa Alifia; Handoyo, Gentur; Ridwan, Agus Wawan; Dawami, Maulana Dwi Nur (Jurnal ILMU DASAR, 2024)
Recent research has revealed that tropical cyclones can develop over eastern Indonesian waters influenced by marine heatwaves and Rossby waves in the atmosphere. However, there is no study documenting tropical cyclones that occur in conjunction with atmospheric Rossby waves (Rossby Atmospheric-Tropical Cyclones) and their association with increased sea surface temperatures in eastern Indonesian waters. This study aims to document the influence of Rossby waves in the atmosphere on the formation of tropical cyclones around the Indonesian region using 5 case studies in 2017-2022, namely: December 2017, January 2020, December 2020, December 2021, and April 2022. This study uses wind data, sea surface temperature, specific humidity, and temperature (2m) obtained from the European Re-Analysis (ERA5) with a temporal and spatial resolution of one hour and 0.25°×0.25°. The identification of Rossby waves is based on the Rossby index issued by the North Carolina Institute for Climate Studies (NCICS). In this study, the Rossby Atmosphere-Tropical Cyclone is grouped into three phases, namely: early phase, mature phase, and late phase, using composite and statistical methods to calculate anomalies. The results showed that in the early phase, the existence of Rossby waves was shown by two twin vortices over eastern Indonesia, which was supported by high specific humidity, warming sea surface temperature (>+0.4°C), and higher surface temperature (>+0.3°C) over Timor. In the mature phase, the twin vortices over eastern waters transformed into a tropical cyclone over the Philippines. In the final phase, specific humidity decreases, sea surface temperature cools (<-0.3°C), and surface temperature decreases (<-0.3°C). The results also prove the crucial role of Timor waters in forming Rossby waves that can grow into tropical cyclones around Indonesia.